(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2023)
Toxic heavy metals are destroying Bangladesh’s coastal sediment due to their ubiquitous nature and accumulation proficiency. The goal of this study was to measure toxic heavy metals iron (Fe), manganese (Mn), nickel (Ni), arsenic (As), cadmium (Cd), lead (Pb), mercury (Hg), copper (Cu), chromium (Cr), zinc (Zn) in Patuakhali coastal sediments of Bangladesh using an atomic absorption spectrometer (AAS) and estimate their ecological risk. The pollution load was calculated using different indices i.e., the pollution factor (CF), the geo-accumulation index (Igeo), the pollution load index (PLI), and the enrichment factor (EF), etc. The spatial distribution was determined using Arc-GIS. The metals concentration range were Fe (10805-36255) mg/kg, Zn (26.91-407.75) mg/kg, Cu (11.25-65.75) mg/kg, Cr (5.425-7.11) mg/kg, Ni (119.94-246.24) mg/kg, Mn (110.88-178.18) mg/kg, As (0.0026-0.097) mg/kg and Hg (0.02-0.12) mg/kg. Cd and Pb concentrations were below the detection limit. Compared to the US-sediment EPA’s quality guideline, this coastal area was highly contaminated with Fe, Cu, and Ni, and moderately contaminated with Mn and Zn. Pollution indices exposed this area was contaminated with Ni and Zn. The metals were distributed in order of Zn>Ni>Fe>Cu>Hg>Cr>As and Ni>Zn>Cu>Fe>Mn>Hg>Cr>As for EF and Igeo respectively. The Potential Ecological Risk Index (PERI) ranged from 94.03 to 241.021, demonstrating a moderate to significant potential ecological risk. Bangladesh J. Sci. Ind. Res. 58(3), 143-154, 2023